Performance Of CVD Coated Carbide Tool By Optimizing Machining Parameters During Turning Titanium Alloy Ti-6AL-4V ELI In Flooded Condition - Sulaiman, Mohd Amri; Mat, Siti Asiyah; Razak, Muhammad Shahmi; Ramle, Zuraimi; Mohamad, Effendi; Che Haron, Che Hassan; A Ghani, Jaharah (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
In metal cutting, one of the important elements which must seriously consider is cutting tools. Carbide cutting tool is widely used in machining process for various metal types. This paper presents the performance of cutting tools in turning Ti-6AL-4V ELI using the CVD coated carbide tool under flooded conditions. Experimental design of this study is based on Factorial method. Two Level Factorial designs were selected to arrange the cutting parameters of cutting speed with a range of 100 to 140m/min, feed rate with 0.15 to 0.20mm/rev, and depth of cut was kept constant at 0.35mm. Flank wear was measured using a three axis microscope. The values were recorded for each length of the workpiece until flank wear (Vbavg) average reaches the tool life criterion, Vbavg = 0.3mm followed by International Standard ISO 3685. From the result obtained, it is found that lowest cutting speed and feed rate resulted in longer tool life while highest cutting speed and feed rate resulted in a much shorter tool life. Based on the ANOVA analysis, cutting speed is the most significant factor followed by feed rate. Mathematical modelling was developed and the error between experimental results and generated model is 19%. The optimum responses are obtained at cutting speed 100m/min, feed rate 0.15mm/rev, and this give out the longest tool life of 15.43minutes while shortest tool life, 4.07 minutes was obtained at cutting speed of 140m/min and feed rate 0.20 mm/rev. The error value of optimization between experimental and model is 0.19%. From this research, even though titanium alloy, Ti-6Al-4V is considered as material with low machinability, there are suitable cutting parameters available to give out the longest tool life thus reducing machining cost.